IMPLEMENTATION OF ARABIC LANGUAGE LEARNING MODELS IN THE KMI GONTOR CURRICULUM AT PONDOK MODERN DARUSSALAM GONTOR CAMPUS 11 ITTIHADUL UMMAH POSO - Rahmat Tulloh Rahmat; Muhammad Nur Asmawi; Atna Akhiryani (SOSIOEDUKASI, 2026)
This study aims to describe the implementation of Arabic language learning models within the Kulliyyatul Mu'allimin Al-Islamiyyah (KMI) Gontor curriculum and to measure its effectiveness in improving students' Arabic competence at Pondok Modern Darussalam Gontor Campus 11 Ittihadul Ummah Poso. Using a descriptive qualitative approach through in-depth interviews and direct observation, the findings reveal four key points: (1) the KMI curriculum implementation aligns with Central KMI Gontor standards through consistent coordination; (2) teachers are required to prepare verified lesson plans (i'dad) prior to instruction; (3) a strong synergy exists between the KMI and the Language Advisory Council (LAC) in building a comprehensive language environment (bi'ah lughawiyyah), encompassing the Ilko Mufradat, Muhadatsah, Barnamij Lughah, and Jasus programs; and (4) the learning model effectively enhances students' Arabic competence across vocabulary mastery, grammatical comprehension, and active communication skills. This effectiveness is supported by an academically-based student classification system, a total immersion approach, and diverse structured language programs.